Social and environmental stressors of cardiometabolic health - Bartoskova Polcrova, Anna; Dalecka, Andrea; Szabo, Daniel; Gonzalez Rivas, Juan Pablo; Bobak, Martin; Pikhart, Hynek (Scientific reports, 2024)
Exposures to social and environmental stressors arise individual behavioural response and thus indirectly affect cardiometabolic health. The aim of this study was to investigate several social and environmental stressors and the paths of their influence on cardiometabolic health. The data of 2154 participants (aged 25-64 years) from the cross-sectional population-based study were analysed. The composite score of metabolic disorders (MS score) was calculated based on 5 biomarkers: waist circumference, blood pressure, fasting blood glucose, HDL-cholesterol, triglycerides. The effects of social stressors (education level, income), environmental stressors (NO2, noise) and behavioural factors (unhealthy diet, smoking, alcohol consumption, sedentary behaviours) on MS score were assessed using a structural model. We observed a direct effect of education on MS score, as well as an indirect effect mediated via an unhealthy diet, smoking, and sedentary behaviours. We also observed a significant indirect effect of income via sedentary behaviours. The only environmental stressor predicting MS was noise, which also mediated the effect of education. In summary, the effect of social stressors on the development of cardiometabolic risk had a higher magnitude than the effect of the assessed environmental factors. Social stressors lead to an individual's unhealthy behaviour and might predispose individuals to higher levels of environmental stressors exposures.
Keywords: Sedentary Behavior; Cross-Sectional Studies; Male; biologické markery; HDL-cholesterol; Risk Factors; Biomarkers; Cholesterol, HDL; psychický stres; krevní glukóza; Adult; dospělí; mužské pohlaví; metabolické nemoci; triglyceridy; Metabolic Diseases; Smoking; Waist Circumference; kardiovaskulární nemoci; lidé; sedavý životní styl; krevní tlak; ženské pohlaví; Humans; Stress, Psychological; rizikové faktory; průřezové studie; Blood Pressure; Environmental Exposure; obvod pasu; Triglycerides; Cardiovascular Diseases; Female; Blood Glucose; lidé středního věku; kouření; vystavení vlivu životního prostředí; Middle Aged